Theoretical insights in catalytic reduction of Cr(VI) using Pd/Fe nitrogen doped mesoporous carbon - Hamideh Hajloo; Hadis Bashiri (Scientific Reports)
Abstract This study explored the kinetics of Cr(VI) conversion into Cr(III) by sodium formate on a nitrogen-doped magnetic mesoporous carbon material infused with Pd and Fe nanoparticles. This study provides the mechanism, kinetic parameters, and optimal conditions for Cr(VI) reduction by employing kinetic Monte Carlo simulations and response surface methodology. It has been proposed that Cr(OH)6 is an intermediate in this reaction. The influences of various factors, such as the initial concentrations of sodium formate and dichromate, pH, and reaction time, on the reaction efficiency were also investigated. These results suggest that the ideal conditions for Cr(III) synthesis involve a synergy of low pH and dichromate levels, a heightened sodium formate concentration, and prolonged reaction periods. The optimal conditions for Cr(III) production on Pd/Fe-NMC surface are pH = 1.37, Reaction time = 161.30 min, Cr2O7 2− initial concentration = 8.3 × 10−4 M, and HCOONa initial concentration = 1.02 M. Under the proposed optimal conditions, the Cr(VI) reduction efficiency of the Pd/Fe-NMC surface was 99.82%.